Pendekatan Uswah Model Supervisi Peningkatan Kinerja Guru PAI di SMP Negeri Kabupaten Nagan Raya - Herman Herman; Farid Wajdi Ibrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
The uswah approach as one of the supervision models in improving PAI (Islamic Education) teachers’ performance is one of the approaches which is based on uswah values as the basic principles in working and serves as a moral force for the supervisors in running their main tasks and functions to supervise PAI teachers. The problem found in the field is that PAI supervisors do not show the attitude and behavior of uswah when supervising, guiding, and improving PAI teachers’ performance. This study is performed in a descriptive design with a qualitative approach. Data were collected through observation, interview, and documentary study meanwhile data analysis was performed by referring to Miles and Huberman which consist of data reduction, computation, and drawing conclusions. In addition, the validity of data was examined through the triangulation of sources, methods, and theories. The result of the study pointed that PAI supervisors have established some uswah values in running the main tasks and functions to supervise PAI teachers through several models of the uswah approach, namely, adorning self with nobility, providing great, friendly, and fair services, guiding and providing advice, and being shy and maintaining self-respect. Whereas the model of doing kindness starting from oneself has not been optimally applied by PAI supervisors so that their attitudes and behavior improving the work performance of PAI teachers are decreasing.